Social media presence and authority of Nigerian University Libraries / Joshua Sani Magoi - Joshua Sani , Magoi (2019)
From the onset of Web 2.0 in 2004 by O’Reilly, usage of social media has become prevalence in academic libraries. Social media tools are used to fulfil a variety of purposes and services aiming towards achieving libraries’ objectives, while people at large use social media tools to stay connected with relations, peer groups and friends. In this digital age, the ubiquity of social media in our lives has captured the imagination and attention of the entire world. Web 2.0 and social media are invariably becoming a more familiar technology that academic libraries in developed countries employ to market their services and resources to their prospective customers, although as observed in this study, this has not been the case in most developing countries in Africa such as Nigeria. Librarians as authors of knowledge are expected to manage their libraries’ online social media presence and to have an effective strategy in place to create their social media authority. In this study, the researcher seeks to examine social media presence in academic libraries in Nigeria and explore how librarians engage with users to create social media authority. The study also seeks to understand academic libraries’ impression on the acceptance and or rejection of social media presence and authority based on a purposive sampling of three federal universities’ libraries in Nigeria. The study adopts a qualitative approach methodology in which interviews, focus groups and web analysis were the instruments used in data collection. Presentation of findings is based on Rogers’ 2003 Diffusion of Innovation (DOI) framework. The results show that libraries and librarians are aware of social media and are already adopting social media platforms for both their official and private purposes. The study also found that although librarians do struggle with issues of acceptance, rejection and non-commitment on their adoption of social media, awareness on the role of social media created positive impacts on the acceptance of this innovation in the libraries and among librarians. On the other hand, negative attitudes of librarians resulted in rejection and non-commitment of social media adoption in the libraries. Findings from web analysis meanwhile show usage of social media are still inadequate as librarians still prefer to engage on their personal platforms. Generally, while some librarians viewed social media presence as an innovation for services and entertainment, quite a few felt it is a medium used for cybercrime and deception. Notwithstanding the findings that established social media presence and authority in academic libraries and among librarians in Nigeria, the findings cannot be generalized as only three libraries were investigated in the study.